Menakar Urgensi Pilkada Asimetris di Papua - Fatoni, Agus (Research and Development Agency Ministry of Home Affairs, 2020)
The local elections (Pilkada) had been implemented since 2005 in Papua, are deemed incapable of resolving problems. On the other hand, the direct local elections' political costs are not small, both from the state's budget and from the candidates to the regions. Implementing direct local elections sometimes creates ineffective governance, especially in areas that do not yet have a mature democracy. The ongoing local democratic system is also often colored by conflict. This research focuses on the urgency of the asymmetric regional election in Papua. This research will explain how important asymmetric local elections (Pilkada) is applied in Papua. Moreover, this study uses a library method and a qualitative approach. The results of this study found several reasons for direct local elections, not yet satisfactory results. Democratization in Papua is still not well consolidated. This research concludes that the warning to hold asymmetric local elections in Papua needs to be considered. However, these choices are not final—contemporary decisions in preparing communities' political and social structures.